Pengaruh Harga dan Kualitas Produk Terhadap Kesejahteraan Petani Manggis di Desa Karacak Melalui Pendapatan - Rio Kartika; Tia Dita; Sholikul Hadi (Economic Reviews Journal, 2026)
This study aims to analyze the direct and indirect influence of price and product quality on the welfare of mangosteen farmers in Karacak Village, with income as an intervening variable. The number of samples was 81 respondents determined through purposive sampling. Data were collected through questionnaires, unstructured interviews, and literature studies. The data analysis method used path analysis with the help of SPSS software version 21. The results of the direct influence study show that there is an influence of price on farmers' welfare and income, while product quality has no effect on farmers' welfare and income. The indirect influence of prices on farmers' welfare through income is quite influential, while the quality of products on farmers' welfare through income is very weak and is considered to have no effect.